Attitudes, Beliefs and Practices Regarding Consumption of Milk and Milk Products among Female Consumers in Mirpur, AJK. - Ali, Ijaz; Anjum, Muhammad Usman; Ahsan Ali, Muhammad; Anwar, Khawar; Muhammad Afridi, Nazar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Various factors influence the quality and safety of milk. However, a detailed study about these factors is lacking in our area. Aim: To elucidate perceptions regarding milk hygiene, milk processing and consumption behaviors. Study design: Descriptive cross-sectional study, Place & duration of study: Mohi-ud-Din Islamic Medical College, Mirpur, AJK, from March to August 2020. Methods: Female staff, patients and attendants were included. A pre-tested and pre-validated questionnaire was used to gather responses. Questions were specifically asked about practices associated with consumption of milk and related products, familiarity with risks associated with consumption of raw milk, practices associated with boiling of milk and milk consumption. Result: There were 130 participants and 75(58%) were educated while 55(42%) were uneducated. Almost all of the educated women were aware of the importance of boiling milk. On the contrary, awareness about usage of boiled milk among uneducated women was 69% while 31% were unaware about the importance of boiling milk. About 58% of study participants consume milk regularly as compared to 42% who were not taking milk regularly. The duration of boiling of milk, for majority of participants, ranged from 05-15 minutes. Side effects experienced by the those consuming raw milk included abdominal pain (62%), diarrhea (23%) and vomiting (15%). Conclusion: The findings suggest that there is a need to encourage sterile milk handling practices and local communities should be closely involved to strengthen their understanding of milk safety. There should be campaigns involving masses to induce behavioral changes among communities about safe and hygienic habits involving handling and usage of milk and its products. The best approach to encourage people towards milk safety will be the boiling of milk.